2013
DOI: 10.1037/a0032260
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Cultural Diversity, Revisited: Recent Publication Trends in Cross-Cultural and Ethnic Minority Psychology

Abstract: Given the increasing proportion of ethnic minority individuals in the United States and psychology's historical reliance on theories derived from Euro American populations, it is important to monitor the status of cultural diversity research. We conducted a 10-year follow-up to Hall and Maramba's (2001) report of cross-cultural (CC) and ethnic minority (EM) publication trends. Comparing data from 1993-1999 and 2003-2009, we found that research on CC and EM issues continues to be underrepresented in the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 14 publications
2
78
0
Order By: Relevance
“…In their review of articles published in APA and APS journals between 1993-1999, Nagayama Hall and Maramba (2001 found that only 6% of articles were focused on racial/ethnic minorities, and only 3% of articles in Developmental Psychology, arguably the leading APA journal focused on developmental science. Hartmann et al (2013) Quintana et al, 2006), it does not seem to have contributed to a major increase in the proportion of studies focusing on racial/ethnic minority youth. Importantly, the emphasis on invisibility should not be taken as an endorsement of racial/ethnic minority youth as passive, or as the seeds of a deficit-oriented research agenda.…”
Section: Expanding the Analytic Toolbox: Intersectionality As An Analmentioning
confidence: 99%
“…In their review of articles published in APA and APS journals between 1993-1999, Nagayama Hall and Maramba (2001 found that only 6% of articles were focused on racial/ethnic minorities, and only 3% of articles in Developmental Psychology, arguably the leading APA journal focused on developmental science. Hartmann et al (2013) Quintana et al, 2006), it does not seem to have contributed to a major increase in the proportion of studies focusing on racial/ethnic minority youth. Importantly, the emphasis on invisibility should not be taken as an endorsement of racial/ethnic minority youth as passive, or as the seeds of a deficit-oriented research agenda.…”
Section: Expanding the Analytic Toolbox: Intersectionality As An Analmentioning
confidence: 99%
“…Such an example probably represents just one of a great many psychological phenomena that are assumed in mainstream psychology to be universal in nature, until investigations of diverse populations reveal otherwise. thus, when one examines the predominant journals in psychology over the past several decades and finds that most of them continue to focus on studies of a very select group of privileged individuals of White or European descent (e.g., Hartmann et al, 2013;nagayama Hall & Maramba, 2001), it becomes not only a pressing scientific problem (e.g., low external validity) but also a challenging social problem (e.g., bias, invisibility, discrimination; Sue, 1999 According to Prilleltensky (1989), a central problem among social scientists is that they often portray themselves as impartial observers whose primary objective is to describe accurately the complex operations of human behavior and then disseminate such insights to the general public. Yet, what may be initially proffered as a purely descriptive finding often can easily turn into an unintended and culturally dangerous prescriptive act.…”
Section: Positive Psychologists and The Study Of Weirdmentioning
confidence: 99%
“…However, a conservative burden-of-proof approach, according to a high standard of evidence, is not only inconsistent with the broad concern and anticipatory stance of the PHT literature (reflected in the qualifier “potentially”)—it could forestall timely attention to potential harm for ethnoracial minorities, irrespective of the extent to which it may be occurring. Given the likely low base rates of iatrogenic treatment, the discipline’s predominant focus on aggregate treatment outcomes, the marginalized status of research funding on socio-cultural rather than intra-individual factors (Nezu, 2005), and continued underrepresentation of ethnoracial minority concerns in the psychological literature (Hartmann et al, 2013), we anticipate that progress for such an empirical endeavor will be slow. This uphill climb is all the more reason for taking seriously, here and now, our call for a serious conversation between these divergent discourses.…”
Section: Discussionmentioning
confidence: 99%